Male Menopause: Concern Needs Attention - Shivakumar, Deekshitha; Nagaraju, Kiran (Indian Journal of Pharmacy Practice)
Andropause, also known as Late-Onset Hypogonadism, is a prevalent occurrence that more men experience as they age. Based on the prevalence of symptoms in the community suggestive of low testosterone, Late-Onset Hypogonadism is diagnosed. The typical sexual symptoms associated with aging include erectile dysfunction, loss of libido, morning erections and decreased testosterone levels. In 1944, the phrase "male menopause" was 1st used to refer to a range of complaints about aging in men that, at least in part, correlated with the climacteric symptoms in women. A number of pathophysiological factors have been identified, including age-related increases in serum Sex Hormone-Binding Globulin Levels, aging of the gonads (accompanied by an increase in luteinizing hormone), the role of visceral adipose tissue in the aromatization of androgen to estrogen and decreased sensitivity of testosterone receptors. This review presents the most recent findings on the benefits and drawbacks of testosterone therapy together with opinions on the predictive relevance of Late-Onset Hypogonadism in evaluating male health.
Keywords: Andropause; Late-onset hypogonadism; Sex hormone-binding globulin levels; Testosterone